Impact of an educational intervention regarding tobacco counseling on dentists and dental students - Tiago Luís Herpich; Eduarda Martins Mendes; Michelle Roxo-Gonçalves; Natan Katz; Janete Dias Almeida; Manoela Domingues Martins; Juliana Romanini; Vinicius Coelho Carrard (Sociedade Brasileira de Pesquisa Odontológica, 2024)
Abstract: The present study aimed to assess the knowledge, attitudes, and perceptions of dental professionals and students regarding tobacco cessation counseling (TCC) after their participation in a continuing education activity (CEA) entitled "Smoking cessation: How does the dentist participate in this decision?" at the Oral Cancer Seminar: Projeto Maio Vermelho 2021. This study utilized a pre-/post-intervention design, including a pre-intervention questionnaire with 20 close-ended questions, an educational intervention, and a post-intervention questionnaire with nine close-ended questions. Descriptive and statistical analyses were performed using SPSS 25 and GraphPad Prism 8 software. The significance level was set at p = 0.05. A total of 94 participants answered the pre-intervention questionnaire and 52 answered both the pre- and post-intervention questionnaires. Most participants reported regularly asking about smoking status (96.8%), providing advice on tobacco risks (96.8%), and offering some counseling to help patients stop smoking (84.0%). Although participants habitually ask about cigarette use, other forms of tobacco consumption are frequently overlooked. Most participants reported never having attended TCC training during their undergraduate studies (67.0%) or after graduation (71.2%). However, 96.2% showed interest in attending TCC training. The perception that motivational counseling by dentists can encourage patients to stop smoking rose from 87.5 to 98.2% (p<0.05) after the educational intervention. In addition, participants' self-confidence in conducting TCC increased from 8.9% to 23.3% (p<0.01). The brief CEA on TCC showed favorable outcomes, enhancing the perception of dentists and undergraduate dental students regarding the effectiveness of counseling for smoking cessation and boosting their self-confidence in providing tobacco counseling.